The Relationship Between Body Fat Percentage And The Level Of Anterior Cruciate Ligament Injury In Athletes Jakarta Regional Training Center - Putranto, Muhammad Arrasyid; Junaidi, Junaidi; Yuliana, Ela; Oktafiranda, Nadya Dwi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to determine the relationship between body fat percentage and level of ACL (Anterior Cruciate Ligament) injury. World Health Organization (WHO) states that 42.2% of major health problems in the community are injuries in children and adults. adults. The most commonly encountered injury generally occurs in the knee ligament ligament, which is a tear of the Anterior Cruciate Ligament. Fat is one of the important components of body composition, if the body fat percentage is not ideal, it can potentially lead to overweight or injury. injury may occur. This study uses the type of research Associative quantitative research with correlation method. The sample in this study using the Total sampling technique. The sample amounted to 25 DKI Jakarta regional training athletes Jakarta who suffered an ACL injury. The results showed that the dependent variable (body fat) and the independent variable (ACL injury rate) there is a value of 0.000 <0.05. value of 0.000 <0.05, which means that there is a significant correlation between the between the variable percentage body fat with the level of ACL injury. Meanwhile, the calculated r value (Pearson correlation) for the relationship between body fat and the level of ACL injury is 0.730. Thus, there is a relationship between body fat percentage and ACL injury rate. Based on the degree of relationship, the percentage of body fat with the level of ACL injury has a strong relationship